2016
DOI: 10.1155/2016/6371856
|View full text |Cite
|
Sign up to set email alerts
|

Does the Beck Cognitive Insight Scale Predict Response to Cognitive Remediation in Schizophrenia?

Abstract: Cognitive remediation therapy (CRT) has emerged as a viable treatment option for people diagnosed with schizophrenia presenting disabling cognitive deficits. However, it is important to determine which variables can influence response to CRT in order to provide cost-effective treatment. This study's aim was to explore cognitive insight as a potential predictor of cognitive improvement after CRT. Twenty patients with schizophrenia completed a 24-session CRT program involving 18 hours of computer exercises and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A recent study by Davidson et al (2016) found that baseline learning potential (LP)—the ability to quickly learn and apply a new skill under testing conditions—significantly predicted skill acquisition in verbal and visuo-spatial memory domains after a 8-week CR intervention in patients with schizophrenia. Furthermore, Benoit et al (2016) demonstrated that higher initial cognitive insight was significantly correlated with greater improvement in speed of processing and visual memory after CR. Burton and Twamley (2015) found no evidence that unawareness of cognitive impairment is a barrier to participation in or ability to benefit from cognitive training, demonstrating no differences in patients with or without neurocognitive insight in terms of treatment utilization and good treatment outcomes in verbal memory and functional capacity (measured by the UCSD Performance-Based Skills Assessment—UPSA).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Davidson et al (2016) found that baseline learning potential (LP)—the ability to quickly learn and apply a new skill under testing conditions—significantly predicted skill acquisition in verbal and visuo-spatial memory domains after a 8-week CR intervention in patients with schizophrenia. Furthermore, Benoit et al (2016) demonstrated that higher initial cognitive insight was significantly correlated with greater improvement in speed of processing and visual memory after CR. Burton and Twamley (2015) found no evidence that unawareness of cognitive impairment is a barrier to participation in or ability to benefit from cognitive training, demonstrating no differences in patients with or without neurocognitive insight in terms of treatment utilization and good treatment outcomes in verbal memory and functional capacity (measured by the UCSD Performance-Based Skills Assessment—UPSA).…”
Section: Resultsmentioning
confidence: 99%
“…Better cognitive insight at baseline was reported to predict greater improvements in cognition following cognitive remediation 63 .…”
Section: Insight and Outcomementioning
confidence: 99%
“…The latter presented with more overconfidence in their own objective errors and were slightly underconfident in correct appraisals (Balzan, 2016). However, the prediction of treatment outcomes by BCIS certainty scores as in our analysis has been found in several studies (Benoit, Harvey, Bherer, & Lepage, 2016; Ohmuro et al ., 2018). Others found that lower BCIS composite scores rather than the sub‐items predicted better treatment outcomes concerning positive symptoms (Perivoliotis et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%